Oscillation Criteria Enhanced for Advanced Half-Linear Dynamic Equations - Taher S. Hassan; Elmetwally M. Elabbasy; Naveed Iqbal; Akbar Ali; Khudhayr A. Rashedi; Amir Abdel Menaem (Journal of Mathematics)
The purpose of this study is to develop new iterative oscillation criteria for second-order half-linear advanced dynamic equations. These findings improve and extend recently established criteria for the same equation by several authors as well as encompass the existing classical criteria for associated ordinary dynamic equations. Some examples are given to show that the outcomes are accurate, practical, and adaptable.